Preparation method and application of composite material based on sodium carboxymethyl cellulose
By optimizing the preparation process and material blending of sodium carboxymethylcellulose, combined with additives such as silica nanoparticles loaded with tea polyphenols, the problem of insufficient film formation performance of sodium carboxymethylcellulose in the prior art was solved, and preparation High-performance composite materials are suitable for food packaging.
Patent Information
- Application Number
- CN202411568593.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-05
- Publication Date
- 2025-02-14
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
In the prior art, the mechanical properties, resistive properties and antibacterial properties of sodium carboxymethylcellulose film are poor, and cannot meet the demand for high-performance materials in food packaging.
By optimizing the preparation process of sodium carboxymethylcellulose, combining the blending of polyethylene glycol, vinyl trimethoxysilane graft modified polylactic acid and starch, silicon dioxide nanoparticles loaded with tea polyphenols, Glycerol and fatty acids are used to prepare composite materials with excellent mechanical properties, barrier properties and antibacterial properties.
The mechanical properties, barrier properties and antibacterial properties of composite materials are significantly improved, making them more suitable for food packaging, with excellent degradability, safety and environmental protection properties.
Smart Images

Figure BDA0005119877840000111 
Figure BDA0005119877840000121 
Figure BDA0005119877840000122
Abstract
Description
Technical Field
[0001] The invention relates to the field of preparation of high-performance composite materials, and in particular to a preparation method and application of a composite material based on sodium carboxymethyl cellulose. Background Art
[0002] The food packaging materials commonly used in daily life are mainly plastic products. Such plastic products are processed from polymer chemicals. Synthetic raw materials with unstable chemical properties will also have a certain impact on human health. In order to be more environmentally friendly and healthy, edible and degradable materials are also prepared by polysaccharides, cellulose, sodium cellulose, proteins and starches in the prior art. Among them, sodium carboxymethyl cellulose is a carboxymethyl derivative of natural polymer chemical cellulose, also known as cellulose gum, which is the main ionic cellulose ether. Its main reaction is: cellulose reacts with NaOH to form alkali cellulose, and then reacts with etherifying agents such as chloroacetic acid to form cellulose ether. Finally, the hydroxyl hydrogen on the six-membered ring of glucose is replaced by carboxyl to form cellulose ether. Because it has many special properties, such as thickening, bonding, film formation, water retention, emulsification, suspension, etc., excellent biocompatibility, harmless to the human body, it is widely used in food, medicine and daily chemical fields. Carboxymethyl cellulose is also widely developed and applied to food packaging due to its film-forming properties to extend the shelf life of food.
[0003] For example, Chinese patent application number CN201910144313.7 discloses a bentonite sodium carboxymethyl cellulose edible film and a preparation method thereof, which uses sodium carboxymethyl cellulose as the main raw material, adds bentonite, glycerol, sodium alginate, carrageenan, and calcium chloride into the solution to make a uniform and stable colloidal solution, and then degassing, pouring the film, drying, and peeling the film. However, the material does not have antibacterial properties and has a single performance. Another example is Chinese patent application number CN201210319713.5, which discloses an alginate-gelatin-sodium carboxymethyl cellulose blend film and a preparation method and application thereof, which is obtained by compounding alginate, gelatin and sodium carboxymethyl cellulose, and has poor performance, which limits its application.
[0004] Therefore, when a single sodium carboxymethyl cellulose film-forming material is used in the prior art, its mechanical properties, resistive properties and antibacterial properties are poor and cannot meet the high-performance requirements of food packaging materials. Therefore, it is necessary to optimize the preparation of sodium carboxymethyl cellulose and the composition of the composite material to make it more suitable for market use needs. Summary of the invention
[0005] Based on this, in order to solve the technical problem that the mechanical properties, resistivity and antibacterial properties of sodium carboxymethyl cellulose film in the prior art are poor and cannot meet the application requirements of food packaging for high performance materials, the present invention provides a preparation method and application of a composite material based on sodium carboxymethyl cellulose, and the specific technical scheme is as follows:
[0006] A method for preparing a composite material based on sodium carboxymethyl cellulose, the method comprising the following steps:
[0007] Extract plant fiber to prepare sodium carboxymethyl cellulose;
[0008] The sodium carboxymethyl cellulose, polyethylene glycol and vinyltrimethoxysilane grafted modified polylactic acid are mixed and stirred to obtain a mixture A;
[0009] Add starch into water, stir evenly to obtain a starch emulsion with a mass percentage concentration of 10% to 15%, gelatinize to obtain a starch gelatinized liquid, then add the mixture A into the starch gelatinized liquid while stirring, stir evenly to obtain a mixture B;
[0010] The silica nanoparticles loaded with tea polyphenols, glycerol and fatty acid are added to the mixture B, and after homogenization, degassing, casting and drying, a composite material based on sodium carboxymethyl cellulose is obtained.
[0011] Furthermore, the preparation method of the sodium carboxymethyl cellulose is as follows:
[0012] The bark is used as raw material, and after pretreatment, it undergoes a first alkalization treatment, washing, and a second alkalization treatment, and cellulose is obtained after washing;
[0013] Add alkali solution to the cellulose, treat at 60°C to 65°C for 20min to 30min, then add ethanol solution of chloroacetic acid, treat at 60°C to 70°C for 1h to 3h, wash, add alkali solution again, treat at 45°C to 60°C for 20min to 30min, then add methanol solution of sodium monochloroacetate, treat at 60°C to 70°C for 1h to 2h, bleach, wash, and dry to obtain sodium carboxymethyl cellulose.
[0014] Furthermore, the conditions of the first alkalization treatment are: adding a sodium hydroxide aqueous solution with a mass percentage concentration of 2% to 5% according to a solid-liquid ratio of (5g to 8g) / 100mL, the temperature is 20°C to 35°C, and the time is 30min to 45min.
[0015] Furthermore, the conditions of the second alkalization treatment are: adding a sodium hydroxide aqueous solution with a mass percentage concentration of 20% to 25% according to a solid-liquid ratio of (5g to 8g) / 100mL, the temperature is 30°C to 40°C, and the time is 1h to 2h.
[0016] Furthermore, the alkali solution is obtained by dissolving sodium hydroxide in isopropanol, and the mass percentage concentration of the sodium hydroxide is 30% to 38%.
[0017] Furthermore, in the methanol solution of sodium monochloroacetate, the mass percentage concentration of sodium monochloroacetate is 45% to 60%.
[0018] Furthermore, the weight ratio of the sodium carboxymethyl cellulose, the polyethylene glycol and the vinyltrimethoxysilane grafted modified polylactic acid is (20-30): (5-9): (15-20).
[0019] Furthermore, the weight ratio of the added amount of the starch to the mixture A is (20-45):100.
[0020] Furthermore, the amount of the silica nanoparticles loaded with tea polyphenols is 1% to 20% of the mass of the mixture B; the amount of the glycerol is 1% to 5% of the mass of the mixture B; and the amount of the fatty acid is 5% to 10% of the mass of the mixture B.
[0021] In addition, the present invention also provides an application based on the sodium carboxymethyl cellulose composite material, and the application is an application of a food packaging film.
[0022] Compared with the prior art, the above technical solution has the following beneficial effects:
[0023] 1. The present invention optimizes the preparation process parameters to prepare sodium carboxymethyl cellulose, which exhibits excellent acid and alkali resistance. Sodium carboxymethyl cellulose with better stability has a significant promoting effect on obtaining high-performance composite materials.
[0024] 2. The present invention mixes the prepared sodium carboxymethyl cellulose with polyethylene glycol and polylactic acid grafted with vinyl trimethoxysilane, and then blends with starch gelatinized liquid. The sodium carboxymethyl cellulose in the composite system can promote the polylactic acid grafted with vinyl trimethoxysilane to form a better crystalline form, and at the same time, can also improve the mechanical properties of the film. The polyethylene glycol can promote the compatibility of carboxymethyl cellulose in polylactic acid grafted with vinyl trimethoxysilane and achieve a certain plasticizing effect. Then, it is mixed with starch and can be evenly dispersed. Under the premise of ensuring a certain flexibility and barrier properties, it plays a significant reinforcing role, and can ensure the mechanical properties of the material as a whole.
[0025] 3. The present invention can impart significant antibacterial properties to the material by adding silica nanoparticles loaded with tea polyphenols, glycerol and fatty acids. Specifically, the silica nanoparticles stably loaded with tea polyphenols have significant antibacterial effects, and there is no need to add artificially synthesized antioxidants with poor stability and chemically synthesized antibacterial agents with toxic side effects, so the safety performance is higher; glycerol can weaken the intermolecular forces, reduce the crosslinking degree of the composite material, and increase the toughness of the composite material; fatty acids help to improve the compatibility of silica nanoparticles loaded with tea polyphenols in the composite material; in addition, silica nanoparticles loaded with tea polyphenols can also be filled in the composite material, further improving the performance of the composite material and making it more widely used.
[0026] 4. The composite material of the present invention has a simple preparation process, excellent degradability, safety and environmental protection, and can be widely used in the field of food packaging to achieve the effect of preserving freshness and quality. DETAILED DESCRIPTION
[0027] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with its embodiments. It should be understood that the specific implementation methods described herein are only used to explain the present invention and do not limit the scope of protection of the present invention.
[0028] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art of the present invention. The terms used herein in the specification of the present invention are only for the purpose of describing specific embodiments and are not intended to limit the present invention. The term "and / or" used herein includes any and all combinations of one or more related listed items.
[0029] A method for preparing a composite material based on sodium carboxymethyl cellulose in one embodiment of the present invention comprises the following steps:
[0030] Extract plant fiber to prepare sodium carboxymethyl cellulose;
[0031] The sodium carboxymethyl cellulose, polyethylene glycol and vinyltrimethoxysilane grafted modified polylactic acid are mixed and stirred to obtain a mixture A;
[0032] Add starch into water, stir evenly to obtain a starch emulsion with a mass percentage concentration of 10% to 15%, gelatinize to obtain a starch gelatinized liquid, then add the mixture A into the starch gelatinized liquid while stirring, stir evenly to obtain a mixture B;
[0033] The silica nanoparticles loaded with tea polyphenols, glycerol and fatty acid are added to the mixture B, and after homogenization, degassing, casting and drying, a composite material based on sodium carboxymethyl cellulose is obtained.
[0034] In one embodiment, the preparation method of the sodium carboxymethyl cellulose is as follows:
[0035] The bark is used as raw material, and after pretreatment, it undergoes a first alkalization treatment, washing, and a second alkalization treatment, and cellulose is obtained after washing;
[0036] Add alkali solution to the cellulose, treat at 60°C to 65°C for 20min to 30min, then add ethanol solution of chloroacetic acid, treat at 60°C to 70°C for 1h to 3h, wash, add alkali solution again, treat at 45°C to 60°C for 20min to 30min, then add methanol solution of sodium monochloroacetate, treat at 60°C to 70°C for 1h to 2h, bleach, wash, and dry to obtain sodium carboxymethyl cellulose.
[0037] In one embodiment, the bark is Morus alba bark.
[0038] In one embodiment, the conditions of the first alkalization treatment are: adding a sodium hydroxide aqueous solution with a mass percentage concentration of 2% to 5% at a solid-liquid ratio of (5g to 8g) / 100mL, the temperature is 20°C to 35°C, and the time is 30min to 45min.
[0039] In one embodiment, the conditions of the second alkalization treatment are: adding a sodium hydroxide aqueous solution with a mass percentage concentration of 20% to 25% at a solid-liquid ratio of (5g to 8g) / 100mL, the temperature is 30°C to 40°C, and the time is 1h to 2h.
[0040] In one embodiment, the alkali solution is obtained by dissolving sodium hydroxide in isopropanol, and the mass percentage concentration of the sodium hydroxide is 30% to 38%.
[0041] In one of the embodiments, the mass percentage concentration of chloroacetic acid in the ethanol solution of chloroacetic acid is 15% to 20%.
[0042] In one of the embodiments, the methanol solution of sodium monochloroacetate has a mass percentage concentration of sodium monochloroacetate of 45% to 60%.
[0043] In one embodiment, the bleaching treatment is to add to a sodium hypochlorite solution with a mass percentage concentration of 0.5%, and treat at 80° C. to 85° C. for 20 min to 35 min.
[0044] In one embodiment, the weight ratio of the sodium carboxymethyl cellulose, the polyethylene glycol and the vinyltrimethoxysilane grafted modified polylactic acid is (20-30): (5-9): (15-20).
[0045] In one embodiment, the stirring speed of the stirring treatment is 100 r / min to 150 r / min, and the stirring time is 45 min to 60 min.
[0046] In one embodiment, the starch is tapioca starch.
[0047] In one embodiment, the weight ratio of the added amount of the starch to the mixture A is (20-45):100.
[0048] In one embodiment, the amount of the silica nanoparticles loaded with tea polyphenols is 1% to 20% of the mass of the mixture B; the amount of the glycerol is 1% to 5% of the mass of the mixture B; and the amount of the fatty acid is 5% to 10% of the mass of the mixture B.
[0049] In one embodiment, the homogenization process is performed at a rotation speed of 1000 r / min to 5000 r / min, a temperature of 60° C. to 85° C., and the homogenization process is performed 1 to 3 times.
[0050] In one embodiment, the drying temperature after the casting is 70° C. to 85° C. and the drying time is 8 h to 10 h.
[0051] In addition, the present invention also provides an application based on the sodium carboxymethyl cellulose composite material, and the application is an application of a food packaging film.
[0052] The composite material obtained in the present application has excellent mechanical properties, barrier properties and antibacterial properties, and can be applied to the field of food packaging.
[0053] The embodiments of the present invention will be described in detail below with reference to specific examples.
[0054] Embodiment 1:
[0055] A method for preparing a composite material based on sodium carboxymethyl cellulose, the method comprising the following steps:
[0056] The mulberry bark is subjected to impurity removal, de-greening and crushing treatment, and then subjected to a first alkalization treatment, wherein the conditions of the first alkalization treatment are: adding a sodium hydroxide aqueous solution with a mass percentage concentration of 3% at a solid-liquid ratio of 5g / 100mL, the temperature is 35°C, and the time is 30min; then the bark is repeatedly washed with clean water, and subjected to a second alkalization treatment, wherein the conditions of the second alkalization treatment are: adding a sodium hydroxide aqueous solution with a mass percentage concentration of 20% at a solid-liquid ratio of 5g / 100mL, the temperature is 35°C, and the time is 2h, and then repeatedly washed with clean water to obtain cellulose;
[0057] Adding a sodium hydroxide isopropanol solution with a mass percentage concentration of 35% of sodium hydroxide to the cellulose, treating at 60° C. for 20 minutes, then adding a chloroacetic acid ethanol solution with a mass percentage concentration of 18% of chloroacetic acid, treating at 60° C. for 2 hours, washing, adding a sodium hydroxide isopropanol solution with a mass percentage concentration of 35% of sodium hydroxide again, treating at 60° C. for 20 minutes, then adding a sodium monochloroacetate methanol solution with a mass percentage concentration of 50%, treating at 60° C. for 2 hours, adding a sodium hypochlorite solution with a mass percentage concentration of 0.5%, treating at 80° C. for 20 minutes, and then repeatedly washing with ethanol with a mass percentage concentration of 75%, and drying to obtain sodium carboxymethyl cellulose;
[0058] The sodium carboxymethyl cellulose, polyethylene glycol and vinyl trimethoxysilane grafted modified polylactic acid are mixed in a weight ratio of 30:7:18, and stirred at a stirring speed of 100 r / min for 45 minutes to obtain a mixture A;
[0059] Adding cassava starch into water, stirring evenly to obtain a cassava starch emulsion with a mass percentage concentration of 15%, gelatinizing to obtain a starch gelatinized liquid, then adding the mixture A to the cassava starch gelatinized liquid while stirring, and the weight ratio of cassava starch to the mixture A is 33:100, stirring evenly to obtain a mixture B;
[0060] Silica nanoparticles loaded with tea polyphenols in an amount accounting for 15% of the mass of the mixture B, glycerol in an amount accounting for 3% of the mass of the mixture B, and fatty acids in an amount accounting for 5% of the mass of the mixture B are added to the mixture B, and the mixture is homogenized three times at a speed of 2000 r / min and a temperature of 60°C, degassed, cast and fixed, and then dried at 85°C for 8 hours to obtain a composite material based on sodium carboxymethyl cellulose.
[0061] Embodiment 2:
[0062] A method for preparing a composite material based on sodium carboxymethyl cellulose, the method comprising the following steps:
[0063] The mulberry bark is subjected to impurity removal, de-greening and crushing treatment, and then subjected to a first alkalization treatment, wherein the conditions of the first alkalization treatment are: adding a sodium hydroxide aqueous solution with a mass percentage concentration of 5% at a solid-liquid ratio of 6 g / 100 mL, the temperature is 30° C., and the time is 35 min; then the bark is repeatedly washed with clean water, and subjected to a second alkalization treatment, wherein the conditions of the second alkalization treatment are: adding a sodium hydroxide aqueous solution with a mass percentage concentration of 22% at a solid-liquid ratio of 6 g / 100 mL, the temperature is 36° C., and the time is 2 h, and the bark is repeatedly washed with clean water to obtain cellulose;
[0064] Adding a sodium hydroxide isopropanol solution with a mass percentage concentration of 36% to the cellulose, treating at 62° C. for 25 minutes, then adding a chloroacetic acid ethanol solution with a mass percentage concentration of 15% to the cellulose, treating at 65° C. for 2 hours, washing, adding a sodium hydroxide isopropanol solution with a mass percentage concentration of 36% again, treating at 55° C. for 30 minutes, then adding a sodium monochloroacetate methanol solution with a mass percentage concentration of 55%, treating at 65° C. for 2 hours, adding a sodium hypochlorite solution with a mass percentage concentration of 0.5%, treating at 85° C. for 25 minutes, and then repeatedly washing with 75% ethanol by mass, and drying to obtain sodium carboxymethyl cellulose;
[0065] The sodium carboxymethyl cellulose, polyethylene glycol and vinyl trimethoxysilane grafted modified polylactic acid are mixed in a weight ratio of 30:9:20, and stirred at a stirring speed of 100 r / min for 50 minutes to obtain a mixture A;
[0066] Adding cassava starch into water, stirring evenly to obtain a cassava starch emulsion with a mass percentage concentration of 15%, gelatinizing to obtain a starch gelatinized liquid, then adding the mixture A to the cassava starch gelatinized liquid while stirring, wherein the weight ratio of cassava starch to the mixture A is 35:100, stirring evenly to obtain a mixture B;
[0067] Silica nanoparticles loaded with tea polyphenols in an amount of 16% by weight of the mixture B, glycerol in an amount of 5% by weight of the mixture B, and fatty acids in an amount of 7% by weight of the mixture B are added to the mixture B, and the mixture is homogenized three times at a speed of 2000 r / min and a temperature of 65° C., degassed, cast and shaped, and then dried at 80° C. for 9 hours to obtain a composite material based on sodium carboxymethyl cellulose.
[0068] Embodiment 3:
[0069] A method for preparing a composite material based on sodium carboxymethyl cellulose, the method comprising the following steps:
[0070] The mulberry bark is subjected to impurity removal, de-greening and crushing treatment, and then subjected to a first alkalization treatment, wherein the conditions of the first alkalization treatment are: adding a 5% sodium hydroxide aqueous solution with a mass percentage concentration at a solid-liquid ratio of 5g / 100mL, the temperature is 35°C, and the time is 45min; then the bark is repeatedly washed with clean water, and subjected to a second alkalization treatment, wherein the conditions of the second alkalization treatment are: adding a 25% sodium hydroxide aqueous solution with a mass percentage concentration at a solid-liquid ratio of 5g / 100mL, the temperature is 35°C, and the time is 2h, and the bark is repeatedly washed with clean water to obtain cellulose;
[0071] Adding a sodium hydroxide isopropanol solution having a mass percentage concentration of 38% sodium hydroxide to the cellulose, treating at 65° C. for 30 minutes, then adding a chloroacetic acid ethanol solution having a mass percentage concentration of 20% chloroacetic acid, treating at 70° C. for 3 hours, washing, adding a sodium hydroxide isopropanol solution having a mass percentage concentration of 38% sodium hydroxide again, treating at 60° C. for 25 minutes, then adding a sodium monochloroacetate methanol solution having a mass percentage concentration of 48%, treating at 70° C. for 1.5 hours, adding a sodium hypochlorite solution having a mass percentage concentration of 0.5%, treating at 82° C. for 30 minutes, and then repeatedly washing with ethanol having a mass percentage concentration of 75%, and drying to obtain sodium carboxymethyl cellulose;
[0072] The sodium carboxymethyl cellulose, polyethylene glycol and vinyl trimethoxysilane grafted modified polylactic acid are mixed in a weight ratio of 30:5:18, and stirred at a stirring speed of 100 r / min for 60 minutes to obtain a mixture A;
[0073] Adding cassava starch into water, stirring evenly to obtain a cassava starch emulsion with a mass percentage concentration of 15%, gelatinizing to obtain a starch gelatinized liquid, then adding the mixture A to the cassava starch gelatinized liquid while stirring, wherein the weight ratio of cassava starch to the mixture A is 40:100, stirring evenly to obtain a mixture B;
[0074] Silica nanoparticles loaded with tea polyphenols in an amount accounting for 20% of the mass of the mixture B, glycerol in an amount accounting for 5% of the mass of the mixture B, and fatty acids in an amount accounting for 9% of the mass of the mixture B are added to the mixture B, and the mixture is homogenized three times at a speed of 3000 r / min and a temperature of 75°C, degassed, cast and fixed, and then dried at 85°C for 8 hours to obtain a composite material based on sodium carboxymethyl cellulose.
[0075] Comparative Example 1:
[0076] The difference between Comparative Example 1 and Example 3 is that conventional commercially available sodium carboxymethyl cellulose is used in Comparative Example 1, and the rest is the same as Example 3.
[0077] Comparative Example 2:
[0078] The difference between Comparative Example 2 and Example 3 is that the preparation method of sodium carboxymethyl cellulose in Comparative Example 2 is different from that in Example 3, and the others are the same as Example 3, wherein the preparation method of sodium carboxymethyl cellulose in Comparative Example 2 is as follows:
[0079] The corn stalks are crushed and then subjected to an alkalization treatment, and the alkalization treatment conditions are: adding a sodium hydroxide aqueous solution with a mass percentage concentration of 25% at a solid-liquid ratio of 5g / 100mL, the temperature is 35°C, and the time is 60min; after repeated washing with clean water, cellulose is obtained;
[0080] A sodium hydroxide isopropanol solution with a mass percentage concentration of 38% of sodium hydroxide is added to the cellulose, and the solution is treated at 65° C. for 30 minutes. Then, a sodium monochloroacetate methanol solution with a mass percentage concentration of 25% of sodium monochloroacetate is added, and the solution is treated at 70° C. for 2 hours. Then, a sodium hypochlorite solution with a mass percentage concentration of 0.5% is added, and the solution is treated at 82° C. for 30 minutes. The cellulose is then repeatedly washed with ethanol with a mass percentage concentration of 75%, and then dried to obtain sodium carboxymethyl cellulose.
[0081] Comparative Example 3:
[0082] The difference between Comparative Example 3 and Example 3 is that polyethylene glycol is not added in Comparative Example 3, and the rest is the same as Example 3.
[0083] Comparative Example 4:
[0084] The difference between Comparative Example 4 and Example 3 is that vinyltrimethoxysilane graft-modified polylactic acid is not added in Comparative Example 4, and the rest is the same as Example 3.
[0085] Comparative Example 5:
[0086] The difference between Comparative Example 5 and Example 3 is that no tapioca starch is added in Comparative Example 5, and the other parts are the same as Example 3.
[0087] Comparative Example 6:
[0088] The difference between Comparative Example 6 and Example 3 is that in Comparative Example 6, silica nanoparticles loaded with tea polyphenols are not added, and the rest is the same as Example 3.
[0089] Comparative Example 7:
[0090] The difference between Comparative Example 7 and Example 3 is that in Comparative Example 7, tea polyphenols are directly used to replace the silica nanoparticles loaded with tea polyphenols, and the rest is the same as Example 3.
[0091] Comparative Example 8:
[0092] The difference between Comparative Example 8 and Example 3 is that in Comparative Example 8, the silica nanoparticles loaded with tea polyphenols are directly replaced with silica nanoparticles, and the rest is the same as Example 3.
[0093] Comparative Example 9:
[0094] The difference between Comparative Example 9 and Example 3 is that no glycerol is added in Comparative Example 9, and the rest is the same as Example 3.
[0095] Comparative Example 10:
[0096] The difference between Comparative Example 10 and Example 3 is that no fatty acid is added in Comparative Example 10, and the rest is the same as Example 3.
[0097] Experimental Example 1:
[0098] The sodium carboxymethyl cellulose prepared in Examples 1 to 3, the conventional commercially available sodium carboxymethyl cellulose in Comparative Example 1, and the sodium carboxymethyl cellulose prepared in Comparative Example 2 were respectively prepared into sodium carboxymethyl cellulose solutions with a mass percentage concentration of 2%. At the same time, hydrochloric acid solutions with pH values of 2, 4, and 6, and sodium hydroxide solutions with pH values of 8, 10, and 12 were respectively prepared, and the corresponding viscosity values were measured using a rotational rheometer. The results are shown in Table 1 below.
[0099] Table 1: Viscosity values of sodium carboxymethyl cellulose (mPa·s)
[0100]
[0101]
[0102] From the data analysis of Table 1, it can be seen that different sodium carboxymethyl celluloses have different degrees of ionization at different pH values, which affects their solubility. However, the present application has better acid and alkali resistance stability than other sodium carboxymethyl celluloses through process optimization.
[0103] Experimental Example 2:
[0104] The thickness of the composite materials of Examples 1 to 3 and Comparative Examples 1 to 10 was all 0.5 mm, and their mechanical properties, barrier properties and antibacterial properties were tested.
[0105] Among them, the tensile strength of the starch film was tested using an intelligent tensile testing machine. Before the test, the sample was placed in a constant temperature and humidity chamber ((23±2)℃, RH=53%) for 48h. The test specifications of the sample and the comparison sample were 15mm×100mm, and the initial clamping distance was set to 80mm.
[0106] The water vapor transmission rate was measured using an automatic water vapor transmission tester. The samples and the comparative samples were placed in a constant temperature and humidity chamber ((23±2)℃, RH=53%) for 48h before testing. The test temperature was 38℃ and the test area was 33.00cm 2 , the relative humidity of the test was 90%, and the weighing interval was 120 minutes. The antibacterial effect was tested by the plate counting method, and the test bacteria were Escherichia coli and Staphylococcus aureus. The results are shown in Table 2 below.
[0107] Table 2: Performance results of composite materials
[0108]
[0109]
[0110] From the data analysis of Table 2, it can be seen that the present application can obtain a composite material with significant mechanical properties, barrier properties and antibacterial properties by optimizing the composition and process. Specifically, different sodium carboxymethyl celluloses are used to prepare composite materials in Comparative Examples 1 and 2, but the tensile strength of the composite material has obvious changes, and the water vapor permeability performance is also significantly affected, indicating that the sodium carboxymethyl cellulose prepared in the present application is relatively less affected by the environment, has high stability, and has a promoting effect on the performance of the composite material. The added components in Comparative Examples 3 to 10 are different from those in Example 3, but they will also affect the performance of the composite material, indicating that after the components in the composite material of the present application are optimized and compounded, the obtained composite material has high performance, and the addition of silica nanoparticles loaded with tea polyphenols can play a certain reinforcing role in the composite material matrix, and can also significantly improve the antibacterial effect of the composite material. On the whole, a high-performance composite material is presented, which has a wider application space.
[0111] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0112] The above-mentioned embodiments only express several implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.
Claims
1. A method for preparing a composite material based on sodium carboxymethyl cellulose, characterized in that: The preparation method comprises the following steps: Extract plant fiber to prepare sodium carboxymethyl cellulose; The sodium carboxymethyl cellulose, polyethylene glycol and vinyltrimethoxysilane grafted modified polylactic acid are mixed and stirred to obtain a mixture A; Add starch into water, stir evenly to obtain a starch emulsion with a mass percentage concentration of 10% to 15%, gelatinize to obtain a starch gelatinized liquid, then add the mixture A into the starch gelatinized liquid while stirring, stir evenly to obtain a mixture B; The silica nanoparticles loaded with tea polyphenols, glycerol and fatty acid are added to the mixture B, and after homogenization, degassing, casting and drying, a composite material based on sodium carboxymethyl cellulose is obtained.
2. The preparation method according to claim 1, characterized in that: The preparation method of described sodium carboxymethyl cellulose is as follows: The bark is used as raw material, and after pretreatment, it undergoes a first alkalization treatment, washing, and a second alkalization treatment, and cellulose is obtained after washing; Add alkali solution to the cellulose, treat at 60°C to 65°C for 20min to 30min, then add ethanol solution of chloroacetic acid, treat at 60°C to 70°C for 1h to 3h, wash, add alkali solution again, treat at 45°C to 60°C for 20min to 30min, then add methanol solution of sodium monochloroacetate, treat at 60°C to 70°C for 1h to 2h, bleach, wash, and dry to obtain sodium carboxymethyl cellulose.
3. The preparation method according to claim 2, characterized in that: The conditions of the first alkalization treatment are: adding a sodium hydroxide aqueous solution with a mass percentage concentration of 2% to 5% according to a material-liquid ratio of (5g to 8g) / 100mL, the temperature is 20°C to 35°C, and the time is 30min to 45min.
4. The preparation method according to claim 2, characterized in that: The conditions of the second alkalization treatment are: adding a sodium hydroxide aqueous solution with a mass percentage concentration of 20% to 25% according to a material-liquid ratio of (5g to 8g) / 100mL, the temperature is 30°C to 40°C, and the time is 1h to 2h.
5. The preparation method according to claim 2, characterized in that: The alkali solution is obtained by dissolving sodium hydroxide in isopropanol, and the mass percentage concentration of the sodium hydroxide is 30% to 38%.
6. The preparation method according to claim 2, characterized in that: The methanol solution of sodium monochloroacetate has a mass percentage concentration of sodium monochloroacetate of 45% to 60%.
7. The preparation method according to claim 1, characterized in that: The weight ratio of the sodium carboxymethyl cellulose, the polyethylene glycol and the vinyltrimethoxysilane grafted modified polylactic acid is (20-30): (5-9): (15-20).
8. The preparation method according to claim 1, characterized in that: The weight ratio of the added amount of the starch to the mixture A is (20-45):
100.
9. The preparation method according to claim 1, characterized in that: The amount of the silica nanoparticles loaded with tea polyphenols is 1% to 20% of the mass of the mixture B; the amount of the glycerol is 1% to 5% of the mass of the mixture B; and the amount of the fatty acid is 5% to 10% of the mass of the mixture B.
10. An application of a composite material based on sodium carboxymethyl cellulose, characterized in that: The sodium carboxymethyl cellulose-based composite material is prepared by the preparation method according to any one of claims 1 to 9, and the application is the application of food packaging film.
Citation Information
Patent Citations
Alginate-gelatin-carboxymethylcellulose sodium blend membrane, and preparation and application thereof
CN102850598A
Edible bentonite carboxymethyl cellulose sodium film and preparation method thereof
CN109929144A
Technology for preparing sodium carboxyl methyl cellulose
CN105542017A
Method for preparing high-viscosity sodium carboxymethylcellulose by taking ramie cellulose as raw material
CN109666077A
Corn starch / sodium carboxymethyl cellulose / fatty acid composite membrane as well as preparation method and application thereof
CN112795057A